2015
DOI: 10.2217/imt.15.13
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Subcutaneous Allergen Immunotherapy With Dermatophagoides Pteronyssinus in Patients With Allergic Rhinoconjunctivitis With or Without Asthma

Abstract: Dermatophagoides pteronyssinus subcutaneous allergen immunotherapy in depot presentation exhibited good safety and tolerability. Group A seemed to show the best profile for further clinical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Similar results could be observed in other studies, where a fast increase in sIgG and sIgG4 can be associated with the effect of blocking IgEbinding to allergens and immune response modification (26,30,31). These results are in line with the immunologic and skin prick test outcomes observed in previous studies with DPT 100% (Allergovac® depot, ROXALL Medicina España S.A., Zamudio, Spain) (22,25). Regarding sIgE determination against Der p 1 and Der p 2, surprisingly a statistically significant increased at final visit was observed.…”
Section: A N U S C P R I T a C C E P T E D F O R P U B B L I C A T supporting
confidence: 91%
“…Similar results could be observed in other studies, where a fast increase in sIgG and sIgG4 can be associated with the effect of blocking IgEbinding to allergens and immune response modification (26,30,31). These results are in line with the immunologic and skin prick test outcomes observed in previous studies with DPT 100% (Allergovac® depot, ROXALL Medicina España S.A., Zamudio, Spain) (22,25). Regarding sIgE determination against Der p 1 and Der p 2, surprisingly a statistically significant increased at final visit was observed.…”
Section: A N U S C P R I T a C C E P T E D F O R P U B B L I C A T supporting
confidence: 91%
“…Studies conducted so far have evaluated the efficacy of subcutaneous immunotherapy based on mite extract and that based on fungal extract separately (19)(20)(21)(22). One of these studies assessed the subcutaneous administration of different doses of long-acting D.…”
Section: Rhinitis Control and Quality Of Life For Patients With Rhinitismentioning
confidence: 99%
“…In addition, this effect increased with the dose of the extract (19). Another study assessed the safety and tolerability of subcutaneous administration of a long-acting D. pteronyssinus extract to patients with allergic rhinoconjunctivitis with or without asthma who are sensitized to this mite (20). The results of the study showed a good safety and tolerability profile of the extract, providing a significant increase in IgG and IgG4 compared with placebo (20).…”
Section: Rhinitis Control and Quality Of Life For Patients With Rhinitismentioning
confidence: 99%